(3SYjO Hf LHjQs (3SjQI PGJjI dchcHI ef YXeGA GdGeI (B/s - (3eLehYI NdjaI ddceHjhJQ(B.s ((3GdbGgQI (B:s (3eLehYI NdjaI ddceHjhJQ(B.s)
.
(3SjfGQjh hMhGQ Cjef SdGeI(B- (3ENQGL YHO GddWja Rcj (B.s
1cd (3eSdSd GFeI GdGSdGe (B.s
All age.
Keywords: (3GdJeKjd GdOQGejs -- (3JdjaRjhf(B.s